Автоматизированная информационная система для торговой компании по продажам компьютеров и комплектующих - Мельников, А. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
The problem of automation of the trading company to sell computers and accessories is considered. In the language of UML the model of information system is developed,. its computer implementation is carried out